Household Waste Management in Buluh Cina Tourism Village Area Public Health Center Pangkalan Baru District, Kampar Regency, 2022 - Firsty Mitalianti; Sumengen Soetomo; Herniwanti Herniwanti; Mitra Mitra; M. Kamali Zaman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to discuss household waste management in Buluh Cina Tourism Village Area Public Health Center Pangkalan Baru District, Kampar Regency, 2022. This research uses qualitative research with phenomenology design. This research is conducted from June to July 2022. The main informants in this study are the Head of the Buluh Cina Village, Village Cadres, and the Buluh Cina Village Community. The key informant in this research is the Acting (Pj.) of the Environmental Health Program, the Technical Implementation Unit of the Pangkalan Baru Public Health Center. Supporting informants in this study are the Head of the Technical Implementation Unit of the Pangkalan Baru Public Health Center, the Environmental Service and the Tourism Office. The data is processed using the triangulation method and analyzed using the stages of data reduction, data presentation, categorization, and data verification. Based on the results of the study, household waste management in Buluh Cina Tourism Village Area Public Health Center Pangkalan Baru District, Kampar Regency, 2022 is not optimal. Therefore, there is a need for support from the Government of the Environment Service, the Tourism Office and the Regional Government in fostering environmental health in Buluh Cina Tourism Village Area.